In Vitro Study of Endothelial Cell Morphology and Gene Expression in Response to Wall Shear Stress Induced by Arterial Stenosis - Mu, Lizhong; Liu, Xiaolong; Liu, Mengmeng; Long, Lili; Chi, Qingzhuo; He, Ying; Pan, Yue; Ji, Changjin; Gao, Ge; Li, Xiaona (Frontiers in Bioengineering and Biotechnology, 2022)
Objectives: We examined the correlation between changes in hemodynamic characteristics induced by arterial stenosis and vascular endothelial cell (EC) morphology and gene expression in straight silicone arteries. Materials and methods: Transparent silicone straight artery models with four degrees of stenosis (0, 30, 50, and 70%) were fabricated. Particle image velocimetry was performed to screen silicone vessel structures with good symmetry and to match the numerical simulations. After the inner surface of a symmetric model was populated with ECs, it was perfusion-cultured at a steady flow rate. A computational fluid dynamics (CFD) study was conducted under the same perfusion conditions as in the flow experiment. The high-WSS region was then identified by CFD simulation. EC morphology in the high-WSS regions was characterized by confocal microscopy. ECs were antibody-stained to analyze the expression of inflammatory factors, including matrix metalloproteinase (MMP)-9 and nuclear factor (NF)-κB, which were then correlated with the CFD simulations. Results: As the degree of vascular stenosis increases, more evident jet flow occurs, and the maximum WSS position moves away first and then back. ECs were irregularly shaped at vortex flow regions. The number of gaps between the cells in high-WSS regions increased. The MMP-9 and NF-κB expression did not differ between vessels with 30 and 0% stenosis. When arterial stenosis was 70%, the MMP-9 and NF-κB expression increased significantly, which correlated with the regions of substantially high WSS in the CFD simulations. Conclusion: Stenotic arteries induce hemodynamic stress variations, which contribute to differences in EC morphology and gene expression. A high degree of vascular stenosis can directly increase inflammatory factor expression.